A cytokine receptor domeless promotes white spot syndrome virus infection via JAK/STAT signaling pathway in red claw crayfish Cherax quadricarinatus. (October 2020) - Liu, Ling-ke; Chen, Xiao-xiao; Gao, Rui-lin; Wang, Ke-jian; Zheng, Wen-yun; Liu, Hai-peng
Abstract: The Janus kinase/signal transducers and activators of transcription (JAK/STAT) signaling pathway is pivotal in immune responses for a variety of pathogens in both vertebrates and invertebrates. Domeless (Dome), as a unique cytokine receptor, involves in the upstream JAK/STAT pathway in invertebrates. In this study, the full-length cDNA sequence of a cytokine receptor Dome was identified from red claw crayfish Cherax quadricarinatus (named as CqDome ), which contained an open reading frame of 4251 bp, encoding 1416 amino acids. The Cq Dome contained extracellular conservative domains of a signal peptide, two cytokine binding modules (CBM), three fibronectin-type–III–like (FN3) domains and a transmembrane region. Tissue distribution analysis showed that CqDome generally expressed in all the tissues selected with a high expression in hemocyte. The gene expression of both the viral immediately early gene ( IE1 ) and a late gene envelope protein VP28 of white spot syndrome virus (WSSV) were significantly decreased after gene silencing of CqDome in crayfish haematopoietic tissue (Hpt) cells, indicating a key role of Cq Dome in promoting WSSV infection. Furthermore, the phosphorylation level of Cq STAT was significantly inhibited by gene silencing of CqDome in Hpt cells, indicating that Cq Dome participated in signal transduction of JAK/STAT pathway in red claw crayfish. These data together suggest that Cq Dome is likely to promote WSSV infection via JAK/STAT pathway, which sheds new light on further elucidation of the pathogenesis of WSSV. Highlights: CqDome promotes the replication of WSSV. CqDome has no effect on the entry of WSSV into Hpt cells. CqDome functions in the activation of JAK/STAT pathway.